Strategies to improve cost and time control using building information model (BIM) - Muhammad, Muhammad Tahir; Haron, Nuzul Azam; Ales @ Alias, Aidi Hizami; Harun, Aizul Nahar (2016)
The demand for the use of a more advanced technology to manage projects information all through their life cycle is very important. An increase in construction sector productivity also means employing modern construction technologies, such as improved and increased mechanisation and such technologies as Building Information Model and Industrialised Building Systems. More also, it is important that skills are improved and intensify to raise productivity that can handle more sophisticated building methods. Presently it is believed to a large extent that the emergence of Building Information Model (BIM) can lead to better productivity in the industry. However, BIM as an alternative technology in Malaysia need to be studied to provide proof that it can satisfy the industry’s need to improve on cost and time control. The aim of this research is to develop strategies that will be used to improve cost and time control in the industry through the use of BIM. This will be achieved through the use of a mixed method of enquiry (semi-structured interview and questionnaire).